Kingdom of the Netherlands : Netherlands; 2009 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the Kingdom of the Netherlands; Netherlands. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
The staff report for the Netherlands' 2009 Article IV Consultation describes the economic developments and policies. State interventions in the financial sector have been broadly appropriate and consistent with a sound fix-it-and-exit approach. Measures have included capital injections, nationalization, and government guarantees. Although systemic risks have been addressed effectively and risk-weighted capital ratios are above required minima, building up equity to levels deemed more adequate in regulatory reform proposals and brisker lending to support the economic recovery may require banks to tap considerable extra capital.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet